2020
DOI: 10.3390/molecules25153343
|View full text |Cite
|
Sign up to set email alerts
|

Extracts Characterization and In Vitro Evaluation of Potential Immunomodulatory Activities of the Moss Hypnum cupressiforme Hedw.

Abstract: Recently, there has been an increasing interest in the chemistry and biological potential of mosses, since a large number of biologically active compounds have been found within these species. This study aimed at examining the chemical composition and immunomodulatory potential (antioxidant, antidiabetic, anti-neuroinflammatory/antineurodegenerative, and antitumor activities) of moss Hypnum cupressiforme Hedw. extracts. Corresponding extracts have been obtained applying Soxhlet extractor. The chemical characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 60 publications
2
44
0
3
Order By: Relevance
“…The available literature on the chemical content of Fontinalis antipyretica is scarce. Comparison with TPC (6.25–18.21 mg/g) of the terrestrial moss Hypnum cupressiforme from low mountain area in Serbia [ 34 ] showed higher TPC in the aquatic moss from the background station. The TPC decreased in the moss over exposure period in all selected reservoirs, while antioxidant activity had no clear trend of gradual decrease in polluted aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The available literature on the chemical content of Fontinalis antipyretica is scarce. Comparison with TPC (6.25–18.21 mg/g) of the terrestrial moss Hypnum cupressiforme from low mountain area in Serbia [ 34 ] showed higher TPC in the aquatic moss from the background station. The TPC decreased in the moss over exposure period in all selected reservoirs, while antioxidant activity had no clear trend of gradual decrease in polluted aquatic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were dried by lyophilisation method to constant weight, and then powdered and weighed (Mass 1). According to previous studies [4,14] moss chemical composition have shown a wide range of various polar and non-polar active compounds, thus solvent properties will significantly be influenced on the chemical composition of their extract. Therefore, three typesof different polarity solvents and corresponding mixture have been used for moss extraction: 96% ethanol, water:ethanol (50:50, vol%), and ethyl acetate.…”
Section: Preparation Of the Extractsmentioning
confidence: 99%
“…Secondary metabolites represent a large group of biologically active compounds that are synthesized as a plant defense mechanism against various microorganisms, insects, herbivores, and different extreme of environmental conditions, as well as for UV protection [11,12]. Some of the currently identified secondary moss metabolites belong to a group of compounds such as phenolic compounds, flavonoids, and terpenoids [4,13] which have been shown to have antioxidant, anti-inflammatory, antitumor, and antibacterial effects PLOS ONE [1,4,14,15]. Flavonoid glycosides such as apigenin and luteolinhave already been confirmed in H. ciliata [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The IC50 value of M. polymorpha was found as 42,7 µg/mL and 93,25 µg/mL for A. californica extracts (Figure 1). Studies on anti-diabetic activity from bryophytes are very limited [36]. This is the first report on the DPP-4 inhibitory activity of the M. polymorpha and A. californica.…”
Section: Dpp-4 Inhibitory Activitymentioning
confidence: 94%
“…Therefore, studies have been focused on discovering the natural DPP-4 inhibitors as alternative treatments for NIDDM [35]. Mosses are rich in phenolic compounds [36]. Many studies have shown the presence of DPP-4 inhibitory activity in many phenolic-rich extracts [37][38][39][40].…”
Section: Dpp-4 Inhibitory Activitymentioning
confidence: 99%